Narrowband ultraviolet B radiation attenuates nucleus pulposus pyroptosis to ameliorate intervertebral disc degeneration by activating NRF2/KEAP1 antioxidant pathway - Zhang, Helou; Tang, Xinyun; Zhou, Huiqing; Zhou, Chengcong; Zhang, Zhiguo; Shen, Shuchao; Fang, Xuliang; Du, Jiazhe; Cheng, Shenghua; Zhang, Jinjie; Xing, Shijia; Chen, Zikun; et al. (Frontiers in Immunology, 2025)
Intervertebral disc degeneration (IVDD) is a major cause of low back pain, with nucleus pulposus (NP) cell pyroptosis—a highly inflammatory form of programmed cell death mediated by NLRP3 inflammasome—playing a crucial role in its pathogenesis by triggering inflammatory cascades and accelerating matrix degradation. Although ultraviolet B (UVB) irradiation has shown therapeutic potential in various inflammatory diseases, its effect on IVDD and underlying mechanisms remained unexplored. In this study, we established a lumbar spine instability (LSI)-induced IVDD mouse model and administered UVB irradiation (315 nm, ~1.0944 mW/cm²) for either 2 minutes (UVB+ group, ~0.13 J/cm²) or 4 minutes (UVB++ group, ~0.26 J/cm²) three times weekly over 8 weeks. UVB treatments effectively attenuated IVDD progression, as evidenced by improved behavioral outcomes, preserved disc height, and maintained structural integrity. Both UVB protocols enhanced extracellular matrix homeostasis, reduced cell apoptosis, and suppressed inflammatory responses, with the UVB+ regimen showing superior efficacy. Mechanistically, UVB significantly inhibited NLRP3-mediated pyroptosis by downregulating NLRP3, ASC, CASPASE1, and GSDMD expression through potent activation of the NRF2/KEAP1 antioxidant pathway. Our findings demonstrate that UVB irradiation effectively ameliorates IVDD by activating the NRF2/KEAP1 pathway and subsequently suppressing NLRP3-mediated pyroptosis, with the 2-minute protocol showing optimal therapeutic effects, establishing UVB irradiation as a promising non-invasive therapeutic strategy for IVDD treatment.